Strategically addressing the needs of agricultural producers in times of financial and legal distress - Swendson, Lana Ann (Kansas State University, 2013)
The purpose of this study was to identify the needs of Kansas' agricultural producers in relation to financial and legal matters at a local level. The following research questions guided this study: 1) what services, identified by local producers, are needed in communities across Kansas to assist producers in times of financial and legal distress; 2) what are the perceptions among producers of the Kansas Agricultural Mediation Services (KAMS); 3) what brand attributes, names, and taglines would appeal to producers for an organization addressing their financial and legal distress; 4) how can organizations effectively market financial and legal services to producers? A qualitative study design was used in order to assess the research questions. Six focus groups were performed throughout the state in three different geographic locations. Participants were selected using purposive sampling in order to have one group of people familiar with the organization (KAMS) currently helping producers with their legal and financial issues and one unfamiliar group in each location. Grunig’s excellence in public relations model served as the conceptual framework for this study. Results of this study concluded that rural Kansas’ communities see a need for service organizations similar to KAMS. Participants value assistance with family farm transition planning as well as financial assistance. Participants saw marketing and promotion of the current services offered just as critical as having the services themselves. Participants felt these services should be marketed through two-way communication channels, such as social media, an organizational representative for face-to-face interaction, and collaboration with extension. Additionally, participants voiced strong opinions about various brand attributes.
Keywords: Financial assistance; Legal assistance; Two-way communication; Family farm transition planning; Branding; Marketing; Communication (0459)